Comparison of Alternative Engine Architectures for Next Generation Supersonic Aircraft - Dario Del Gatto; Stylianos Adamidis; Christos Mourouzidis; Stephen Brown (Engineering Proceedings, 2025)
The present paper illustrates the design space exploration of a supersonic mixed-flow turbofan engine for civil applications. The aircraft platform selected is a 10-passenger business jet, cruising at Mach 1.6. To overcome noise limitations at take-off, an alternative engine architecture with additional exhaust nozzle variability, to overcome the take-off noise limit, is proposed. The fully variable area nozzle configuration allows for an overall 15% weight reduction against a partially variable area nozzle architecture. In terms of overall aircraft mission fuel burn, it shows an 8% mission fuel burn reduction against the partially variable area nozzle architecture, with a final fuel efficiency of 11.4 pax-mile/us gallon.